Case formulation using pattern-based formulation (PBF) methodology: clinical case 4. (December 2018) - Fernando, Irosh; Lampe, Lisa
Objectives: To provide a further example of the utility of the pattern-based model in formulation, and to introduce some further patterns. Methods: A case study was carried out using the Pattern-based Formulation (PBF). Results: Based on the case of a patient with a past history of trauma who developed late onset somatic symptoms, post-traumatic stress disorder and major depression, the PBF approach enabled development of a comprehensive formulation to explain the patient's current presentation. Four patterns were utilised. Conclusions: The PBF method of using patterns as building blocks enables development of a psychobiological formulation that can accommodate considerable complexity. PBF represents a broadly applicable method that may assist psychiatry trainees and others to develop good quality formulations.